Uji Kelayakan Pengembangan Buku Ajar Tematik Berbasis Inkuiri Kontekstual untuk Siswa Sekolah Dasar - Amalia Rizki Ardiansyah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
This research aims to determine a thematic text book's feasibility based on elementary school students' contextual inquiry. The model used in the development is Dick Carey, which has been simplified by the researcher into nine development stages as follows: (1) identifying objectives, (2) conducting learning analysis, (3) analyzing students and learning context, (4) formulating learning objectives, (5) developing assessment instruments, (6) developing learning strategies, (7) developing and selecting learning materials,( 8) conducting formative evaluations, and (9) product revisions. The product development then goes through a validation test by the material expert, design expert, and user expert by using different expert instruments. The result of the feasibility test has been analyzed descriptively. The result shows that the thematic textbook based on contextual inquiry with the percentage of feasibility from the material expert was 97,6% (valid), from design expert was 78,27% (valid), and from the user was 98,96% (valid). The result shows that the textbook which has been developed was feasible and can be implemented with little revision.